Seasonality of Freeze Tolerance in a Subarctic Population of the Wood Frog, Rana sylvatica - Jon P. Costanzo; M. Clara F. do Amaral; Andrew J. Rosendale; Richard E. Lee (International Journal of Zoology)
We compared physiological characteristics and responses to experimental freezing and thawing in winter and spring samples of the wood frog, Rana sylvatica, indigenous to Interior Alaska, USA. Whereas winter frogs can survive freezing at temperatures at least as low as −16°C, the lower limit of tolerance for spring frogs was between −2.5°C and −5°C. Spring frogs had comparatively low levels of the urea in blood plasma, liver, heart, brain, and skeletal muscle, as well as a smaller hepatic reserve of glycogen, which is converted to glucose after freezing begins. Consequently, following freezing (−2.5°C, 48 h) tissue concentrations of these cryoprotective osmolytes were 44–88% lower than those measured in winter frogs. Spring frogs formed much more ice and incurred extensive cryohemolysis and lactate accrual, indicating that they had suffered marked cell damage and hypoxic stress during freezing. Multiple, interactive stresses, in addition to diminished cryoprotectant levels, contribute to the reduced capacity for freeze tolerance in posthibernal frogs.